PERFORMA TELEMARKETING PT BFI FINANCE BANJARMASIN - Ni Nyoman Suarniki; Dwi Wahyu Artiningsih (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2020)
Abstract, One change to an established system or order will have a broad impact on the output and performance of the system, such as the era of the COVID-19 pandemic that has not yet ended. The purpose of this study is to find out how much telemarketing contribution to BFI Finance Banjarmasin in an effort to maintain the amount of distribution of funds (sales). This research uses a quantitative design with an exploratory approach, the company's customers are 2,800 people, and the customers who are willing to participate in this study are 100 people, with a simple random technique, and the data analysis uses analytic descriptive analytic. This research found that, BFI Finance does not yet have telemarketing special officers, marketing staff do all sales activities. Either long distance (telemarketing) or meet directly with prospective customers / customers. There are no special officers in the database of customers or prospective customers, all are still working concurrently. Telemarketers of BFI Finance Banjarmasin are already working in accordance with the tasks assigned in the job description with good performance. There was a decrease in disbursement of funds, most likely because competitors were more attractive and perhaps more intense in prospecting prospective customers.